2012
DOI: 10.1371/journal.pone.0042601
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p21 Activated Kinase (PAK) Reduces Airway Responsiveness In Vivo and In Vitro in Murine and Human Airways

Abstract: The p21-activated protein kinases (Paks) have been implicated in the regulation of smooth muscle contractility, but the physiologic effects of Pak activation on airway reactivity in vivo are unknown. A mouse model with a genetic deletion of Pak1 (Pak1 −/−) was used to determine the role of Pak in the response of the airways in vivo to challenge with inhaled or intravenous acetylcholine (ACh). Pulmonary resistance was measured in anesthetized mechanically ventilated Pak1 −/− and wild type mice. Pak1 −/− mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…24 103105 One likely driver of PAK1 activation in IBD is TNFα 88. PAK1 activation triggers signalling pathways which drive proliferation, initiate cell migration or block apoptosis, and may contribute to a loss of intestinal barrier function.…”
Section: Paks In Gi Diseasesmentioning
confidence: 99%
“…24 103105 One likely driver of PAK1 activation in IBD is TNFα 88. PAK1 activation triggers signalling pathways which drive proliferation, initiate cell migration or block apoptosis, and may contribute to a loss of intestinal barrier function.…”
Section: Paks In Gi Diseasesmentioning
confidence: 99%
“…Similarly, PAK1 also phosphorylates myosin light chains, in addition to the myosin phosphatase targeting subunit MYPT1, to promote smooth muscle contractility . Studies in mice have shown that decreased expression of Myh11, Mylk1, or PAK1 each individually result in impaired SMC contractility and GI motility . SRF‐myocardin complexes regulate transcription of many smooth muscle contractile proteins including both MYH11 and MYLK1 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies in mice have shown that decreased expression of Myh11, Mylk1, or PAK1 each individually result in impaired SMC contractility and GI motility. 25,32,34 SRFmyocardin complexes regulate transcription of many smooth muscle contractile proteins including both MYH11 and MYLK1. 25,26,35,36 Although we did not observe a significant change in myocardin mRNA in samples from patients with idiopathic gastroparesis, we did see a significant decrease in SRF mRNA (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Knockout or pharmacological inhibition of Pak reduces tone of airway smooth muscle (Hoover et al . ). Introduction of Pak3 in permeabilized smooth muscle induces a Ca 2+ ‐independent contraction, possibly via phosphorylation of caldesmon (Van Eyk et al .…”
Section: Introductionmentioning
confidence: 97%